55 Anticancer Fruits, Vegetables, Beverages, Oils and Spices - Maliheh Najari Beidokhti (International Journal of Phytomedicine, 2013)
Cancer is one of the most devastating diseases, and despite good understanding of the molecular basis of the disease and advances in treatment, globally cancer is still a major cause of death. It has been estimated that 30–40 percent of all cancers can be prevented by lifestyle and dietary measures alone and a diet rich in fruits and vegetables is associated with a reduced risk of many common forms of cancer. Several in vitro and in vivo studies have demonstrated the antitumor properties of various fruit and vegetable extracts and beverages. Epidemiological data suggest that ingestion of bioactive compounds from fruits and vegetables, such as polyphenols and terpenes, may contribute to reduce the incidence of cancer in humans. The mechanisms by which these compounds inhibit tumourgenesis include inhibition of tumour cell mediated protease activity, attenuation of tumour angiogenesis, induction of cell cycle arrest and promotion of apoptosis. In addition, it has been reported that combining natural compounds with chemotherapeutic agents is a promising strategy to enhance the inhibition of tumour survival. Also a wide variety of phenolic substances derived from spice possess potent antimutagenic and anticarcinogenic activities. Such spices have been known to be effective on large intestine, liver, stomach, breast, skin, bladder, and colon cancer. Hence, an attempt has been made to review some fruits, vegetables, beverages, oils and spices used for the prevention and treatment of cancer.